Review paperCyclooxygenase-2 expression and its association with thyroid lesions - Krawczyk-Rusiecka, Kinga; Lewiński, Andrzej (Archives of Medical Science, 2010)
Cyclooxygenase (COX), also known as prostaglandin H synthase, catalyses the formation of prostaglandins from arachidonic acid. It can be expressed in response to various stimuli, such as hormones, mitogens, cytokines, other inflammatory mediators and growth factors. The product of COX-2 activity has been implicated in carcinogenesis by promoting angiogenesis, inhibiting apoptosis, increasing cell invasion and stimulating cell proliferation. It has also been proved that the regular intake of non-steroidal anti-inflammatory drugs (NSAIDs) decreases the risk of developing colon and breast cancers. Thus, it speaks for an important role of COX-2 in growth processes of various types of neoplasms. The connection between COX-2 activity and carcinogenesis has also been examined in human thyroid neoplasms. COX-2 overexpression has been reported in thyroid cancers and also in inflammatory conditions. In consequence there is significant interest whether COX-2 could be of importance as a molecular marker of malignancy in the case of thyroid carcinoma.